Growth and lignan accumulation of Phyllanthus amarus (Schum. & Thonn.) cultured in vitro photoautotrophically as affected by light intensity and photoperiod - Duy, Pham Minh; Quynh, Nguyen Thi (Academia Journal of Biology, 2014)
Light intensity and photoperiod are two important factors to the growth and secondary metabolite accumulation of in vitro plants, especially under photoautotrophic micropropagation. Internodal segments carrying 1 leaf of in vitro Phyllanthus amarus plants were used as explants. Four explants were put on MS medium with half strength macro elements and without sugar and vitamins, in a Magenta box-type vessel (V = 370 ml). There were two holes (Ф = 1 cm) covered by Millipore membranes (Ф = 0.45 µm) on the vessel lid. Perlite was used as supporting material. The experiment was carried out with 3 different light intensities (80, 120 or 160 µmol m-2 s-1) in combination with 3 levels of photoperiod (8, 12 or 16 hours per day), under room temperature of 25 ± 2oC and relative humidity of 50%. On day 40, Phyllanthus amarus plants grew better under higher PPF and longer photoperiod. Increased fresh weight and dry weight, stem diameter and shoot lenght of in vitro plants were the highest under the PPF of 160 μmol m-2 s-1 and the photoperiod of 16 hours per day. Phyllanthin, hypophyllanthin and niranthin contents were the largest when plants were cultured under the PPF of 80 µmol m-2 s-1 and the photoperiod of 12 hours per day.